COMMENTS ON ALON BEN-MEIR'S "THE CASE FOR AN ISRAELI-PALESTINIAN-JORDANIAN CONFEDERATION, WHY NOW AND HOW". (December 2022) - Saras, Issa
This essay draws attention to some of the current conditions in Palestine as these relate to, and potentially affect, the arguments contained in Alon Ben-Meir's (2022) recent proposal for an Israeli-Palestinian-Jordanian Confederation. In contrast to the level of free speech in Israel, the situation in Palestine is significantly more guarded and less understood abroad. I argue that this should be taken into account in any and all proposals for conflict resolution between the two peoples. My aim is to highlight some important aspects of the proposal and encourage Israelis and Palestinians alike to investigate more deeply what is happening in Palestine in order to assist in generating policy solutions that consider the concerns and the goals of both peoples in the context of a permanent solution to their conflict .